2022
DOI: 10.2196/37682
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Influencing Factors on Acceptance of eHealth Pain Management Interventions Among Patients With Chronic Pain Using the Unified Theory of Acceptance and Use of Technology: Cross-sectional Study

Abstract: Background Chronic pain is a complex disease with high prevalence rates, and many individuals who are affected do not receive adequate treatment. As a complement to conventional therapies, eHealth interventions could provide many benefits to a multimodal treatment approach for patients with chronic pain, whereby future use is associated with the acceptance of these interventions. Objective This study aims to assess the acceptance of eHealth pain managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
5
8
2
Order By: Relevance
“…In addition, patients who are still moderately to significantly impaired after COVID-19 infection expressed higher acceptance than patients in currently good condition. This is in line with the results of Stoppok et al 27 showing higher acceptance in more burdened individuals affected by chronic pain. In addition, patients with moderate to severe symptoms during the initial COVID-19 infection also showed higher acceptance.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, patients who are still moderately to significantly impaired after COVID-19 infection expressed higher acceptance than patients in currently good condition. This is in line with the results of Stoppok et al 27 showing higher acceptance in more burdened individuals affected by chronic pain. In addition, patients with moderate to severe symptoms during the initial COVID-19 infection also showed higher acceptance.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the comparison between the original and the extended UTAUT model indicated that the extended version, which includes additional predictors, is able to explain a higher level of variance of acceptance. This result has been previously described in other studies, 19,27 whereas another study reported opposite results. 26…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations